Presepsi Mahasiswa : Pemotivasian Belajar Melalui Repositori Dengan Hasil Belajar Pada Masa Pandemik COVID-19 - Andar Gunawan Pasaribu (Jurnal Christian Humaniora, 2020)
This study aims to develop strategies learning motivational from the repository for student learning outcomes.  . This research was conducted on IAKN Tarutung students by using the development research method. Development is carried out through stages, namely symbol, development tools, ease of accessing the repository.  completeness of lecture materials, and the Effective repository.   The results of testing the use of applications repository with an average value of 88%.